Nurse care for the hospitalized elderly's spiritual dimension - Sylvia Maria Cardoso Bastos Veras; Tânia Maria de Oliva Menezes; Raúl Fernando Guerrero-Castañeda; Mateus Vieira Soares; Florencio Reverendo Anton Neto; Gildásio Souza Pereira
ABSTRACT Objective: to analyze the nurse care for the spiritual hospitalized elderly's dimension. Method: a qualitative study, based on Jean Watson's Theory of Human Caring. The study included 17 nurses working in a geriatric center in Salvador City, Bahia State, Brazil. The collection of testimonies occurred between January and April of 2018, through an interview. Results: spiritual care were dialogue, encouragement and respect for religious activities, embracement, empathy. One of the obstacles to providing this care was the lack of preparation in accessing the elderly's spiritual dimension. Final considerations: spirituality is a dimension of human and holistic nursing care. Caring for the spirit contributes to foster transpersonal care. The difficulty may be in the lack of nurses' preparation. It is necessary that they cultivate and live their own spirituality, transmitting the understanding in each care relationship.